New Zealand : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper examines the external linkages of the New Zealand economy. Empirical results from vector autoregressive models suggest that economic activity in Australia tends to have more of a significant direct impact on New Zealand than does activity in the United States. Fluctuations in the U.S. GDP, however, appear to be transmitted to New Zealand indirectly through their effects on the Australian economy. Financial linkages also have been important components in transmitting shocks from Australia and the United States to the New Zealand economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet